Desenvolvimento de instrumentos e procedimentos analíticos automáticos com detecção quimiluminescente e espectrofotométrica - Borges, Eduardo Poggi e (Universidade Federal de São Carlos, 2004)
In the present work is described computer-controlled flow systems designed for process control of L-alanine synthesis and for bromide determination in this amino acid, presented as a contaminant species. Since the analytical systems were computer controlled, all the procedures steps, such as, stopped flow, dilution, pH adjustment, analyte concentration and sample clean up, were performed without operator assistance. In order to carry out chemiluminescent reaction, a simple and low cost device (ca. US$ 150) that comprises two photodiodes fixed in lab-made Perspex flow cell was proposed. Regarding L-alanina determination, it was exploited the L-amino acid oxidize enzyme reaction. In this system, the sample was injected into a carrier stream, passing through a column packed with this immobilized enzyme. The product of the amino acid oxidation, hydrogen peroxide, was determined by the chemiluminescent reaction with luminol. The interfering species of the enzymatic reaction was suppressed by coupling in the flow system a column packed with a strong anionic resin. A linear concentration range between 0.5 and 25 mmol L-1 and a 0.08 mmol L-1limit of detection were some of the analytical characteristics of this system. Regarding the chemiluminescent bromide determination, the procedure was based on bromide oxidation by chloramine-T followed by the reaction of the formed bromine with luminol. In order to minimize the interference of alanina in the chemiluminescent reaction, a column packed with a strong anionic resin was used for analyte concentration and sample clean up. The analytical features obtained were a linear range between 0.010 and 1.000 mg L-1 (r=0.999) and a limit of detection of 1 µg L-1 of Br-. Also in this work is reported the development and the characterization of a lowcost device for NO2 determination in atmosphere exploiting the Griess-Slatzman reaction. The NO2 was sampled from the atmosphere by a porous membrane tube, which was also used as flow cell. To monitor the colored-forming reaction, it was constructed a dual-wavelength LED-based spectrophotometer. With the proposed device it was obtained a 0.5 ppbv limit of detection of NO2, a low reagent consumption (100 µL per determination), 5 % relative standard deviation for 5 ppbv NO2 sample concentration and long term stability, at least 168 hours without requiring calibration procedure.
Development of a device and automatic analytical procedures exploiting chemiluminescent and spectrophotometric detection
Keywords: Instrumentação; Análise por injeção de fluxo; Espectrofotometria; Quimiluminescencia; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA